The power of odour cues in shaping fine-scale search patterns of foraging mammalian herbivores. (29th July 2020) - Orlando, Cristian Gabriel; Tews, Ashley; Banks, Peter; McArthur, Clare
Abstract : Foraging by mammalian herbivores has profound impacts on natural and modified landscapes, yet we know little about how they find food, limiting our ability to predict and manage their influence. Mathematical models show that foragers exploiting odour cues outperform a random walk strategy. However, discovering how free-ranging foragers exploit odours in real, complex landscapes has proven elusive because of technological constraints. We took a novel approach, using a sophisticated purpose-built thermal camera system to record fine-scale foraging by a generalist mammalian herbivore, the swamp wallaby ( Wallabia bicolor ). We tested the hypothesis that odour cues shape forager movement and behaviour in vegetation patches. To do this, we compared wallaby foraging in two odour landscapes: Control (natural vegetation with food and non-food plants interspersed) and +Apple (the same natural vegetation plus a single, highly palatable food source with novel odour (apple)). The +Apple treatment led to strongly directed foraging by wallabies: earlier visits to vegetation patches, straighter movement paths, more hopping and fewer stops than in the Control treatment. Our results provide clear empirical evidence that odour cues are harnessed for efficient, directed search even at this fine scale. We conclude that random walk models miss a key feature shaping foraging within patches.